Investigation on the modelling approach for variable-density lattice structures fabricated using selective laser melting. (15th December 2021) - Song, Jun; Tang, Qian; Feng, Qixiang; Ma, Shuai; Guo, Fuyu; Han, Quanquan
Graphical abstract: Highlights: Proposing a clustering-based modelling approach to generate variable-density lattice structures. Only several cells were needed to be determined rather than all cells designed one by one during the modelling approach. A variable-density lattice beam was designed and manufactured using selective laser melting. Finite element analysis and three-point bending tests showed the beam samples superior in mechanical performance. Abstract: Selective laser melting (SLM)-produced variable-density (VD) lattice structures are deemed a promising solution to lightweight design. However, due to the large number of cells in the structures, designing VD structures is still time-consuming and exhibits poor adaptability to external load. Therefore, in order to decrease the number of design variables in VD design, this paper proposed a modelling approach for VD lattice structures manufactured using SLM. The stress values provided by finite element analysis (FEA) were grouped according to k-means clustering, where the sizes of lattice cells in the same group remain identical. Then the relative densities of cells' in all groups are obtained and the VD model is generated. By taking the design of a VD lattice beam as an example, the feasibility of the proposed method was verified by conducting FEA and three-point bending tests on SLM-produced Ti6Al4V samples, as well as using morphological observation measures. The results show that the number of design variables for reconstructing the beam was decreased from 125 to 8, and the VD samples reached the designed carrying capacity and also presented superior lightweight performance compared with their isovolumetric homogenous counterparts.